2022
DOI: 10.1007/s00330-022-08916-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk of acute kidney injury after contrast-enhanced computerized tomography: a systematic review and meta-analysis of 21 propensity score–matched cohort studies

Abstract: Objectives Intravenous application of contrast media is part of a wide spectrum of diagnostic procedures for better imaging quality. Clinical avoidance of contrast-enhanced imaging is an ever-present quandary in patients with impaired kidney function. The objective of this study was to estimate the risk for acute kidney injury (AKI), dialysis and mortality among patients undergoing contrast-enhanced CT compared to propensity score–matched controls (i.e. contrast-unenhanced CT). Selected cohort st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 57 publications
0
9
0
1
Order By: Relevance
“…In the meta-analysis by Obed et al [ 15 ] comprising the data of 169,455 patients, computed tomography with CM usage was not associated with a higher risk of AKI (OR: 0.97, 95%CI: 0.85–1.11, p = 0.64). Only hypertension and an eGFR of ≤30 mL/min/1.73 m 2 predisposed patients to the development of CI-AKI.…”
Section: Discussionmentioning
confidence: 99%
“…In the meta-analysis by Obed et al [ 15 ] comprising the data of 169,455 patients, computed tomography with CM usage was not associated with a higher risk of AKI (OR: 0.97, 95%CI: 0.85–1.11, p = 0.64). Only hypertension and an eGFR of ≤30 mL/min/1.73 m 2 predisposed patients to the development of CI-AKI.…”
Section: Discussionmentioning
confidence: 99%
“…58 However, several radiology organisations are revising how contrast-enhanced studies are implicated in acute kidney injury. 59,60…”
Section: Intraoperative Implementation Of Algorithmic Ai In Irmentioning
confidence: 99%
“…Due to new information in these studies, the 2018 Swedish guidelines regarding CI-AKI following CT were revised during 2022. This revision is based on: A 2022 systematic review and meta-analysis of 21 retrospective propensity score-matched controlled studies regarding the risk of AKI after contrast medium (CM)-enhanced and unenhanced CT (2) revealed the following: (i) an increased risk of AKI after CM-enhanced CT compared with controls undergoing unenhanced CT in patients with an estimated glomerular filtration rate eGFR) <30 mL/min/1.73 m 2 (odds ratio [OR] = 1.68, 95% confidence interval [CI] = 1.29–2.19; P = 0.0001) with an absolute risk increase of 4%; and (ii) no evidence of an increased risk of AKI, dialysis, or mortality after CM-enhanced CT in patients with an eGFR ≥45 mL/min/1.73 m 2 , without comments regarding the eGFR interval of 30–44 mL/min/1.73 m 2 . A 2021 multicenter emergency department propensity score-matched study (3) of approximately 68,000 patients revealed the following: (i) an increased risk of AKI withing 48–72 h and dialysis within one month after CM-enhanced CT in patients with eGFR <45 mL/min/1.73 m 2 compared with the non-enhanced CT group; and (ii) no evidence of an increased risk of AKI or dialysis after CM-enhanced CT in patients with an eGFR ≥45 mL/min/1.73 m 2 . A systematic review performed by the Radiological Society of the Netherlands graded retrospective propensity score-matched controlled CT studies as low evidence due to risk of selection bias between the CM-enhanced and non-enhanced group (4). Thus, the scientific evidence is still uncertain regarding toxicity of intravenous CM. The total post-CM-induced incidence of AKI in four randomized hydration protocol studies (Tables 1 and 2) of elective examinations (95% outpatients) including CT (n = 1613), and peripheral and coronary angiography and interventions (n = 289).…”
Section: Introductionmentioning
confidence: 99%
“…A 2022 systematic review and meta-analysis of 21 retrospective propensity score-matched controlled studies regarding the risk of AKI after contrast medium (CM)-enhanced and unenhanced CT (2) revealed the following: (i) an increased risk of AKI after CM-enhanced CT compared with controls undergoing unenhanced CT in patients with an estimated glomerular filtration rate eGFR) <30 mL/min/1.73 m 2 (odds ratio [OR] = 1.68, 95% confidence interval [CI] = 1.29–2.19; P = 0.0001) with an absolute risk increase of 4%; and (ii) no evidence of an increased risk of AKI, dialysis, or mortality after CM-enhanced CT in patients with an eGFR ≥45 mL/min/1.73 m 2 , without comments regarding the eGFR interval of 30–44 mL/min/1.73 m 2 .…”
Section: Introductionmentioning
confidence: 99%